Jazakumu Allahu Khairan: Stairway to Heaven ( Book 7) by Manal Shehab - Manal Shehab (Stairway to heaven, book. 7., 2012)
Manal Shehab’s Stairway to Heaven series and Zeynep Haydan’s colourful illustrations make perfect picture books for your Islamic library.